National biodiversity strategy and action plan of St. Lucia : protecting the future (The Ministry CastriesLC, 2000)
Seeks to optimise the contribution of biological diversity to the sustainable economic, social and cultural development of St. Lucia.
Keywords: BIODIVERSITY